Neuromyelitis optica spectrum disorder: epidemiology, pathogenesis, diagnosis, treatment, and prognosis - J. Čemerkaitė; I. Kaukėnaitė; R. Liutkevičienė (Neurologijos seminarai)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare acute inflammatory disease of the central nervous system (CNS) predominantly affecting the optic nerve and the spinal cord. The main pathogenetic mechanism of NMOSD is the interaction of aquaporin-4 (AQP4), an integral astrocyte plasma membrane protein, and antibodies against aquaporin-4 (AQP4-IgG). The incidence of NMOSD ranges from 0.039 to 0.73 per 100,000 adult population, and the highest incidence estimates are associated with African and Asian ethnicities. The median age at presentation is 32-45 years, the disease affects women more often than men. Clinical manifestations of the disease depend on lesions in those areas of the CNS where AQP4 is most pronounced: spinal cord, optic nerves, dorsal medulla, brainstem, thalamus, and hypothalamus. Initially, NMOSD typically presents with optic neuritis or transverse myelitis, or, less commonly, a combination of both. Diagnosis of NMOSD is based on clinical symptoms, MRI findings, and detection of AQP4-IgG antibodies in serum. All acute attacks should be treated with high-dose intravenous methylprednisolone, i.e., 1 gram per day for three to five consecutive days. Maintenance treatment to prevent NMOSD relapses includes azathioprine, mycophenolate mofetil, and rituximab. Recent results of randomised clinical trials with monoclonal anti- bodies such as inebilizumab, satralizumab, tocilizumab, and eculizumab have proved their efficacy and safety in maintenance treatment of NMOSD. Factors leading to a worse prognosis include the severity of the first attack, higher number of relapses in the first two years, older age at the disease onset, and association with other autoimmune disorders. The overall 10-year mortality after diagnosis is 20-25%. Challenges in treating NMOSD during the COVID-19 pandemic include clinical relapses, susceptibility to infection, and disease management during this critical period.